1992
DOI: 10.1073/pnas.89.10.4673
|View full text |Cite
|
Sign up to set email alerts
|

In vitro replication of adeno-associated virus DNA.

Abstract: An in vitro assay for adeno-aociated virus (AAV) DNA replication has been developed. The substrate is a plasmid containing the duplex form of AAV DNA in pBR322. The AAV insert is excised or rescued from the pas by extracts of uninfected cells. Replication was assayed by production of full-length excised AAV DNA resistant to Dpn I (ii) Only the excised AAV insert was replicated; pBR322 sequences were not. (iv) Replication was dependent on the presence of the AAV terminal repeat. (v) If the terminal 55 bases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…Some of these effects have been attributed to the viral nonstructural Rep proteins, which are central to the regulation of AAV DNA replication and transcription (2,18,36,44,46). Two of the Rep proteins (Rep68 and Rep78) have been associated with the preferential integration of AAV genomes into a region of the long or q arm of human chromosome 19 (27)(28)(29)48).…”
mentioning
confidence: 99%
“…Some of these effects have been attributed to the viral nonstructural Rep proteins, which are central to the regulation of AAV DNA replication and transcription (2,18,36,44,46). Two of the Rep proteins (Rep68 and Rep78) have been associated with the preferential integration of AAV genomes into a region of the long or q arm of human chromosome 19 (27)(28)(29)48).…”
mentioning
confidence: 99%
“…In wt AAV, Rep68/78 causes the rearrangement of the AAVS1 site and replication of the ITR cassette before site-specific integration. 22,[50][51][52] Thus, additional copies of the transgene cassette can be generated and integrated. Further, in AAV vectors, which lack rep sequences, the ITR cassette is often integrated into actively transcribed regions of the genome.…”
Section: Integration Of 100 Kb Gene Via Hsv/aav Amplicon Vector a Oehmentioning
confidence: 99%
“…AAV ITRs and Rep68 or Rep78 have been shown to catalyze replication as well as site-specific integration of the ITR-flanked DNA into the genome. [22][23][24][25] Recent experiments have demonstrated that a 138 bp fragment of p5, the integration efficiency element (p5IEE) containing the p5 promoter, can also mediate site-specific integration with a 10-100-fold higher efficiency than the ITRs. 26 HSV/AAV hybrid vectors combine the HSV-1 elements ori S and pac with the AAV ITRs flanking the gene of interest and the rep-gene placed outside the ITR cassette.…”
Section: Introductionmentioning
confidence: 99%
“…As a parvovirus AAV replicates its DNA by a 'rolling hairpin' mechanism [7][8][9]. The terminal repeats (TR) elements, of 145 base pairs, located at each terminus of the linear AAV DNA genome, are cis required for AAV DNA replication [10].…”
Section: Introductionmentioning
confidence: 99%